Towards Quantum-Secured Permissioned Blockchain: Signature, Consensus, and Logic - Sun, Xin; Sopek, Mirek; Wang, Quanlong; Kulicki, Piotr (Entropy (Basel, Switzerland), 2019)
While Blockchain technology is universally considered as a significant technology for the near future, some of its pillars are under a threat of another thriving technology, Quantum Computing. In this paper, we propose important safeguard measures against this threat by developing a framework of a quantum-secured, permissioned blockchain called Logicontract (LC). LC adopts a digital signature scheme based on Quantum Key Distribution (QKD) mechanisms and a vote-based consensus algorithm to achieve consensus on the blockchain. The main contribution of this paper is in the development of: (1) unconditionally secure signature scheme for LC which makes it immune to the attack of quantum computers; (2) scalable consensus protocol used by LC; (3) logic-based scripting language for the creation of smart contracts on LC; (4) quantum-resistant lottery protocol which illustrates the power and usage of LC.